Pre-Service Teachers’ Literary Work: Input a Literary Resource Material (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
During their formative years, children exposed to various engaging literary activities can explore and comprehend the vastness of the world and its myriad wonders. This research seeks to assess the literary works produced by pre-service teachers as the foundation for a reading plan aimed at early elementary school students. Thirty participants, including teachers and parents, evaluated the literary pieces using formalist, reader-response, and moral-philosophical approaches.Formalist Approach:The formalist approach focuses on the internal structure and elements of the literary works, such as plot, characterization, setting, language, and symbolism. The evaluators assessed the literary pieces for their coherence, consistency, and effectiveness in conveying the intended message.Reader-Response Approach:The reader-response approach emphasizes the individual reader’s interpretation and response to the literary works. The evaluators explored their personal experiences, emotions, and connections to the stories, providing valuable insights into the potential impact of these works on young readers.Moral-Philosophical Approach:The moral-philosophical approach examines the ethical and societal implications of the literary works. The evaluators considered the values, morals, and life lessons presented in the stories, evaluating their suitability for promoting positive character development in early-grade schoolers.The unanimous evaluation of all nine literary works as highly acceptable underscores their potential effectiveness in engaging and educating young readers. The stories were well-written, age-appropriate, and rich in themes that resonate with children’s experiences and imaginations.The developed reading plan provides a structured framework for introducing early-grade students to literary works. It outlines activities and discussions that encourage active engagement with the stories, fostering comprehension, critical thinking, and appreciation for literature.The recommended use of the reading plan in assessing children’s reading skills offers a valuable tool for educators. By observing their responses to the stories, teachers can gain insights into their students' comprehension, vocabulary, and ability to connect with literary themes.This research highlights the significance of early exposure to meaningful literary activities in shaping children’s understanding of the world and their place within it. Evaluating pre-service teachers' literary work and developing a reading plan provides valuable resources for educators seeking to cultivate a love for literature and promote literacy development among early-grade schoolers.
Keywords: reading plan; early reading and literacy; pre-service teachers creative works